Service for Assessing Rank for High School Teacher Promotion at the Education and Culture Office of Central Sulawesi Province - Fitriani Abdullah (Formosa Journal of Sustainable Research, 2022)
This study aims to identify and describe the Assessment Service for High School Teacher Promotion at the Education and Culture Office of Central Sulawesi Province. Usefulness of this research Theoretically and Practically. The Literature Review explains the concept of Service Quality, Public Service, Teacher Paradigm, Teacher Status and Position, Requirements to make a Teacher, Teacher Duties and Functions, Teacher Rights and Obligations, Teacher Credit Points. Flow of Thought by the theory of Zeithml, Parasuraman and Berry which includes Tangibles, Reability, Responsiveness, Assurance and Empathy. Research using qualitative methods, Research Location at the Education and Culture Office of Central Sulawesi Province, Research Time for three months, Informants are elements of ASN (State Civil Apparatus Related to Research), Operational definition of the concept, namely, Tangibles or direct evidence related to problems of facilities and infrastructure that is still lacking due to damage due to the earthquake and Reability indicators related to disciplinary problems of existing employees who do not arrive on time, while the Responseviness, Assurance and Empathy indicators are quite good. Thus, it can be concluded that the quality of promotion services for teachers at the Education and Culture Office of Central Sulawesi Province is good, sourced from informants, but as researchers have made in-depth observations, there are still various deficiencies and obstacles in the process of promotion services. towards high school teachers based on various existing aspects